Expert’s Testimony Evidence in the Criminal Justice Process in Indonesia - Prananto, Iksan; Sunardi, Sunardi; Muhibbin, Moh. (International Journal of Law, Environment, and Natural Resources, 2023)
This study aims to analyze the position of expert testimony as evidence in the criminal justice process. The type of research in this research is normative. The nature of the research is descriptive. The results of his research are that the position of expert testimony as evidence is basically a gate, especially for investigators in determining whether this gate will be opened or not or whether will it last first. What an expert explains is the conclusions from a known situation according to his expertise. Thus, the substance of the expert's statement becomes the investigator's authority to evaluate it at the investigative level. Because, sometimes in the investigation process expert testimony is sidelined because the witness testimony is more dominant, of course, this will affect the process of proving the trial.